Birth asphyxia measured by the pH value of the umbilical cord blood may predict an increased risk of attention deficit hyperactivity disorder. (17th April 2017) - Mikkelsen, Susanne Hvolgaard; Olsen, Jørn; Bech, Bodil Hammer; Wu, Chunsen; Liew, Zeyan; Gissler, Mika; Obel, Carsten; Arah, Onyebuchi
Abstract: Aim: Although birth asphyxia is a major risk factor for neonatal and childhood morbidity and mortality, it has not been investigated much in relation to attention deficit hyperactivity disorder (ADHD). We examined whether birth asphyxia measured by the pH of the blood in the umbilical artery cord was associated with childhood ADHD. Method: A population‐based cohort of 295 687 children born in Finland between 1991 and 2002 was followed until December 31, 2007. ADHD was identified by the International Classification of Diseases, 10th edition, as a diagnosis of hyperkinetic disorder. We examined the risk of ADHD with varying pH values using Cox regression, taking time trends into consideration. Results: When compared to the reference group, a pH value below 7.10 was significantly associated with an increased risk of ADHD. The strongest risks were observed among children with a pH value <7.15 and a gestational age of <32 weeks. The pH value did not contribute much to the risk among children with an Apgar score of 0–3. Conclusion: Birth asphyxia, defined by low pH value, may predict an increased risk of ADHD in childhood. The association between the pH value and ADHD was homogenous when stratified by gestational age and the Apgar score.